Natura mediów masowych i zagrożenia związane z ich wpływem w świetle głównych tez teorii Marshalla McLuhana - Pytko, Marek Jan (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The hidden, at first glance imperceptible nature of the 20th-century electronic media, and, to an even greater degree, of the digital media of 21st century, often becomes a cause of threats that may bring painful results. Such results, generated by the uninformed use of the media, are related not only to the transmitted contents, but also, in particular, to the form of the media influence. This is due to the fact that, as Marshall McLuhan observes, the media constitute special extensions of the human senses that, by nature, are part of the nervous system. If the equilibrium of the human senses is purposefully disturbed in the way controlled by those media, e.g., through various games, the effects on the user are easy to foresee. Together with the claim that “the medium is the message,” the Canadian media scholar shows that a change in the form of a given medium entails a change in the pace, scale, pattern, and model of life related to this medium. All those change accelerations produce a definite yet imperceptible effect, transforming patterns of behaviour and habits, and by the same token converting the model, routines, conventions, paradigms, practices, and ideals present in the life of an individual and a society. Therefore, in a long perspective, it is the form of a medium that exerts a generally much more determining influence on the changes than the contents transmitted. If we consider the global scale and a growing potential for manipulation, especially in the context of the new media, the perspective of their impact becomes immense and, as it opposes the complementary development of the human being, may generate far-reaching threats.